(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
This article examines the life expectancy of the population for the period 2005-2020. We will analyze the influence of various factors and its dynamics. Calculate the average growth rate and check the multicollinearity of the factors. It is revealed that it affects life expectancy.